NICC - null (IEE Colloquium on How to Compete and Connect: Understanding the Engineering of Telecommunications Network Interconnection, 1997)
Background Intensive care nurses are at high risk of fatigue and sleep disturbances due to irregular shift patterns and high levels of occupational stress. Although aromatherapy is increasingly used as a holistic intervention, evidence regarding its effects on fatigue and sleep quality among nurses remains limited. Aim This study aimed to evaluate the effects of a chamomile-lavender essential oil blend and vetiver oil on fatigue and sleep quality in intensive care nurses experiencing fatigue and sleep disturbances. Study design A randomised, placebo-controlled, single-blind mixed-methods study was conducted in Türkiye. Participants were assigned to the chamomile-lavender, vetiver or placebo (jojoba oil) group (n = 36 per group). Aromatherapy massage was administered once daily before bedtime for 4 weeks. Fatigue and sleep quality were assessed using the Visual Analogue Scale (VAS), Piper Fatigue Scale (PFS) and Pittsburgh Sleep Quality Index (PSQI). Qualitative data were collected using semi-structured interview forms. Results A total of 108 nurses were randomly selected; 12 participants withdrew, and 96 completed the study. Post hoc power analysis demonstrated an effect size of f = 0.462 and statistical power of 0.984. Median VAS fatigue severity scores (minimum-maximum) decreased from 7.5 to 2.0 in the chamomile-lavender group, from 7.0 to 2.0 in the vetiver group and from 8.0 to 4.0 in the placebo group (pre-test p = 0.361; post-test p < 0.001). PSQI scores decreased from 10.41 to 4.69, 10.91 to 4.63 and 10.78 to 6.84, respectively (pre-test p = 0.634; post-test p < 0.001). PFS scores decreased from 5.98 to 2.94, 5.58 to 2.76 and 5.80 to 4.37, respectively (pre-test p = 0.616; post-test p < 0.001). Total PFS scores demonstrated significant group and time effects (p ≤ 0.001). Likewise, PSQI scores improved significantly over time, with both a significant group effect (p = 0.018) and a highly significant time effect (p < 0.001). Qualitative findings indicated that nurses experienced greater relaxation, improved sleep initiation and reduced fatigue. Conclusions Aromatherapy using a chamomile-lavender blend or vetiver oil may be an effective intervention for reducing fatigue and improving sleep quality among intensive care nurses. Future studies could utilise multicentre, double-blind designs, longer follow-up periods and objective sleep measures such as actigraphy. Relevance to clinical practice Aromatherapy is a complementary and integrative therapy (CIT) intervention that has been associated with reductions in fatigue and improvements in sleep quality in previous studies. The findings of this study suggest that aromatherapy may represent a feasible and nonpharmacological strategy to support the well-being of intensive care nurses. However, further high-quality randomised controlled trials incorporating multicentre designs, long-term follow-up and objective outcome measures are required before aromatherapy can be recommended for routine clinical implementation. Trial registration ClinicalTrials.gov identifier: NCT06474793.